fractopo: A Python package for fracture network analysis - Ovaskainen Nikolas (Open Journals, 2025)
In the Earth’s crust, networks of approximately planar discontinuities, fractures, form intricate networks where they cross-cut and abut each other. These fractures control the stability of the crust and act as pathways for fluid flow and subsequently, transfer of geothermal heat and contaminants. Fractures can be observed from exposed bedrock surfaces where these discontinuities appear as two-dimensional fracture traces. Digitizing these fracture trace observations (e.g., from drone imaged outcrops) results in georeferenced two-dimensional trace vector datasets (i.e., fracture networks), which offer a cross-sectional window into the three-dimensional networks within the bedrock.